Delayed Presentation of Renocolic Fistula at 4 Months after Blunt Abdominal Trauma - Sang Don Lee; Tae Nam Kim; Hong Koo Ha (Case Reports in Medicine)
Causes of previously reported reno-colic fistulas included primary renal and colonic pathologic states involving infectious, malignant or other inflammatory processes. However, reno-colic fistula after renal injury is extremely uncommon. We report an unusual delayed presentation of reno-colic fistula that occurred at 4 months later after blunt abdominal trauma.